New biostimulant for flowering and ripening in coffee (Coffea arabica L.) - Chacón-Villalobos, Yeiner; Chacón-Sancho, Adriana; Vargas-Chinchilla, Mariano; Cerdà-Subirachs, Josep Ma.; Hernández-Pérez, Ricardo (Agronomía Mesoamericana, 2021)
Introduction. Climatic variables have been affecting coffee cultivation on Central American region; high temperatures, high levels of ultraviolet light (UV), rainfall and its intensity have caused serious problems for the development of the crop. There are physiological imbalances that cause losses in stimulation and flower setting, and depending on the variety, production losses can exceed 60 %. Objective. To determine the effect of a new biostimulant on flowering, ripening and fruit quality in coffee crop. Materials and methods. The work was carried out during the years 2018 and 2019, at La Hilda farm, Murillo lot, located in Alajuela province, canton San Pedro of Poas, Costa Rica, under agroecological management. The effect of the application of a foliar biostimulant product was evaluated at a dose of 3 l ha-1, certified for organic production agriculture, was evaluated. Two treatments, two and three applications of bioestimulant were used and compared with an absolute control. The parameters evaluated were: stimulation and floral set, productive nodes for the next cycle, and fruits quality. Results. There were no significant statistical differences between the the two biostimulant treatments (3 l ha-1) in contrast to the control. When evaluating the greater fruit set and fruit quality production, when applications were made during the flowering and fruiting phase, homogeneity of ripening, and a greater number of cherries per branch were obtained. Conclusion. The use of the new biostimulant with two foliar applications on the coffee crop stimulated the flowering, ripening, and fruit quality with respect to the untreated control.